Pengaruh Magnesium Stearat, Talk atau Kombinasinya Terhadap Waktu Hancur dan Disolusi Tablet Prednison Pada Campuran Interaktifnya - Ilham Kuncahyo (Jurnal Farmasi Indonesia, 2009)
Interactive mixtures give advantages for the mixtures containing low dose drug such as prednisone as it guarantee homogeneity, stability and increase the dissolution of prednisone. Flowability and compactibility of the interactive mixtures are relatively good, it can be directly compressed to produce tablet. The addition of lubricant / glidant of Mg stearat , talc or their mixture as the cohesive materials to the prednisone-granule interactive mixtures produce prednisone- granule-lubricant/ glidant which affect the tablet properties such as disintegration time and release of the drug. Based on these matter, a study was done to examine effect of Mg stearat, talc or their mixtures to the disintegration time and dissolution of prednisone interactive mixtures tablet. For the investigation of these effects, experiments were done using optimization approach based on simplex lattice design with Mg stearate and talc as the independent variable. The experiments data were implemented into the equation relation to the simplex lattice design : Y= a(A) + b (B) + ab (A) (B). Based on the coefficient value of the disintegration time and drug dissolution equations, profiles are made, lubricant/glidant effects on the disintegration time and drug dissolution can be analyzed. Magnesium stearate cause prednisone interactive mixtures disintegration time tablet are more longer than talc, although the affect interaction is relativity more little. Magnesium stearate compared with talc gives C30 value and DE-60, although the interaction gives affect relativity more little.